Missionary Stories and the Formation of the Syriac Churches - Saint-Laurent, Jeanne-Nicole Mellon (Book collections on Project MUSE., 2015)
"This book analyzes the hagiographic traditions of six missionary saints in the Syriac heritage: Thomas, Addai, Mari, Simeon of Beth Arsham, Jacob Baradaeus, and Ahoudemmeh. Saint-Laurent studies a body of legends about missionaries' voyages in the Syrian Orient and illustrates their shared symbols and motifs. Revealing how these texts encapsulate the concerns of the communities that wrote them, she draws attention to the role of hagiography as a malleable genre that was well suited for the idealized presentation of the beginnings of Christian communities. Hagiographers, through their reworking of missionary themes, assert autonomy, orthodoxy, and apostolicity for their individual civic and monastic communities, posturing themselves in relationship to the rulers of their empire and other competing forms of Christianity. She argues that missionary hagiography is an important and neglected source for understanding the development of the East and West Syriac ecclesiastical bodies: the Syrian Orthodox Church and the Church of the East. Many of these Syriac-speaking churches remain today in the Middle East and India, with diaspora communities in Europe and North America. While Saint-Laurent focuses on late antiquity in Missionary Stories and the Formation of the Syriac Churches, her work opens up further study of the role of saints and stories as symbolic links between ancient and modern traditions"--Provided by publisher.